Development of Large-Scale Green Energy Sources with Grid Integration: Practices and Challenges - Arunagirinathan, Sumithara; Subramanian, Chitra (Journal of Electronics and Informatics, 2023)
Planning and evaluation are crucial for the successful amalgamation power grid and the energy sources that are renewable. The tasks posed by intermittency, variability, and uncertainty of solar and wind generation can affect the power system’s operational economics. Therefore, conducting planning and evaluation studies before the actual solar and wind power construction can help identify the maximal integration capacity of the renewable source that are feasible for a specific power grid. The planning should include an analysis on the power systems flexibility and adequacy, that involves the analysis of the resource characteristics, reliability analysis and production simulation. This analysis can help identify the technical and economic challenges of integrating renewable energy sources and provide beneficial plans for independent system operators, investors and government to make operational decisions as well as planning towards an advanced dissemination of renewable power. The design of the electrical system is also essential and should include the analysis of the power flow and its stability, the mode of connection as well as its stability, transmission design, interconnection and power quality analysis. These design considerations ensure the stability and the reliability while integrating renewable energy sources. Future efforts must also take into account technical elements like modelling, methods, and indices used for evaluation that are connected to incorporation planning as well as evaluation. Advances in technology and modelling techniques can help improve the accuracy and reliability of integration planning and evaluation studies, which can help facilitate a higher penetration of renewable power in the power grid.